2019
DOI: 10.3389/fnins.2019.00461
|View full text |Cite
|
Sign up to set email alerts
|

A Nutraceutical Strategy to Slowing Down the Progression of Cone Death in an Animal Model of Retinitis Pigmentosa

Abstract: Retinitis pigmentosa (RP) is an inherited retinal dystrophy characterized by progressive degeneration of the visual cells and abnormalities in retinal pigment epithelium, the vision is lost slowly, and the final outcome is total blindness. RP primarily affects rods, but cones can also be affected as a secondary effect. Photoreceptor cell death is usually triggered by apoptosis, however the molecular mechanisms linking the rod degeneration to the secondary cone death are poorly understood. Possible causes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Furthermore, interaction between photoreceptors and RPE cells is critical for maintaining visual function, and its alteration can lead to compromised vision. Our group has already demonstrated that antioxidants can delay photoreceptor degeneration in a mouse model of retinitis pigmentosa [21][22][23], and this protective effect certainly requires the integrity of RPE [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, interaction between photoreceptors and RPE cells is critical for maintaining visual function, and its alteration can lead to compromised vision. Our group has already demonstrated that antioxidants can delay photoreceptor degeneration in a mouse model of retinitis pigmentosa [21][22][23], and this protective effect certainly requires the integrity of RPE [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The diluted solutions were daily prepared; moreover, mice were weekly weighted, and water intake was daily monitored during the six-month treatment. The dosage of NAR (100 mg/kg) has been selected based on previous in vivo experiments [13,27] and in accordance with papers of others [28][29][30][31]. In particular, NAR has been dissolved in DMSO 40 mg/mL and diluted in water up to 0.4 mg/mL, to assure a daily dosage of 100 mg/kg.…”
Section: In Vivo Chronicmentioning
confidence: 99%
“…Some of these approaches try to correct or replace the genetic defect (gene or stem cell-based therapies) or to slow down the IRD progression (nutritional supplements, neurotrophic factors, antioxidants, etc.). In particular, several antioxidant formulations including curcumin, Tauroursodeoxycholic Acid (TUDCA), vitamin A, vitamin A in combination with docosahexaenoic acid (DHA), lutein, etc., have been used to mitigate the degenerative process in RP models and patients [116,[144][145][146][147][148][149][150].…”
Section: Inherited Retinal Dystrophiesmentioning
confidence: 99%
“…Antioxidants 2020, 9, x FOR PEER REVIEW 6 of 28 with docosahexaenoic acid (DHA), lutein, etc., have been used to mitigate the degenerative process in RP models and patients [116,[144][145][146][147][148][149][150]. 4.…”
Section: Inherited Retinal Dystrophiesmentioning
confidence: 99%